2017
DOI: 10.1007/s10067-017-3571-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal system manifestations in juvenile systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease which may involve gastrointestinal system (GIS). The aim of this study was to present GIS manifestations of pediatric SLE patients. The medical files of 69 children with SLE followed between January 2011 and January 2016 were reviewed. All fulfilled the Systemic Lupus International Collaborating Clinics criteria. All patients (≤18 years of age) with GIS manifestations were included. GIS manifestations were observed in 19 (27.5%) out of 69 SLE patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
3
16
2
2
Order By: Relevance
“…Of note, the majority of our patients had a Results are presented in n (%) and median (range), *P -value according to Bonferroni correction for multiple comparisons (p < 0.0033), SLEDAI-2 K -SLE Disease Activity Index 2000 complete response to the classical AIH prednisone and azathioprine combination therapy. Reinforcing this finding none of our patients had hepatic failure, portal hypertension and cirrhosis suggesting that AIH phenotype in lupus was a non-severe pattern [1,3]. Additionally, none of our cSLE patients had anti-LKM1 antibodies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Of note, the majority of our patients had a Results are presented in n (%) and median (range), *P -value according to Bonferroni correction for multiple comparisons (p < 0.0033), SLEDAI-2 K -SLE Disease Activity Index 2000 complete response to the classical AIH prednisone and azathioprine combination therapy. Reinforcing this finding none of our patients had hepatic failure, portal hypertension and cirrhosis suggesting that AIH phenotype in lupus was a non-severe pattern [1,3]. Additionally, none of our cSLE patients had anti-LKM1 antibodies.…”
Section: Discussionsupporting
confidence: 82%
“…Childhood-onset systemic lupus erythematosus (cSLE) is an autoimmune and inflammatory disease that affects multiple organs and systems, including liver [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlap syndrome was usually used in the context of overlap of autoimmune hepatitis with primary sclerosing cholangitis (PSC) or primary biliary cholangitis (PBC), also called autoimmune sclerosing cholangitis (ASC). Although the case number is few, overlapping case of SLE and AIH has been occasionally diagnosed and reported (12, 13). Pediatric sclerosing cholangitis also has autoimmune features similar to AIH type 1, and the differential diagnosis depends on cholangiography (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, there seems to be a non–relapsing association in the case reports of AIH-SLE overlapping in the recent years. Sönmez et al (12) reported 8 pediatric SLE-AIH overlapping patients with good response to immunosuppressive treatment and good prognosis of AIH. Since the case number is still few, further discussion should be done if more cases reported in the future.…”
Section: Discussionmentioning
confidence: 99%